Social media 101 : tactics and tips to develop your business online - Brogan, Chris (Hoboken, New Jersey : Wiley, 2010)
100 ways to tap into social media for a more profitable business. In Social Media 101, social media expert and blogger Chris Brogan presents the best practices for growing the value of your social media and social networking marketing efforts. Brogan has spent two years researching what the best businesses are doing with social media and how they're doing it. Now, he presents his findings in a single, comprehensive business guide to social media. You'll learn how to cultivate profitable online relationships, develop your brand, and drive meaningful business. Brogan shows you how to build an ef.
Above all else : people -- What social media does best -- Social media does not replace marketing strategy -- Making business sense of social media -- Social media as personal power -- Social media for your career -- Threading some trends together -- The vital importance of your network.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Internet marketing; Social media -- Economic aspects; Customer relations -- Management; Information technology -- Management; Marketing sur Internet; x; Technologie de l'information -- Gestion; BUSINESS & ECONOMICS -- Marketing -- Telemarketing; BUSINESS & ECONOMICS -- Marketing -- Multilevel; BUSINESS & ECONOMICS -- Mail Order; BUSINESS & ECONOMICS -- Marketing -- Direct; BUSINESS & ECONOMICS -- E-Commerce -- Internet Marketing; Customer relations -- Management; Information technology -- Management; Internet marketing; Social media -- Economic aspects